An Entanglement Study of Superposition of Qutrit Spin-Coherent States - M. Jafarpour (Journal of Sciences, Islamic Republic of Iran)
Considering generalized concurrence as the criterion of entanglement, we study entanglement properties of superposition of two qutrit coherent states, as a function of their amplitudes. These states may attain maximum entanglement or no entanglement at all, depending on the choice of the parameters involved. The states revealing maximum entanglement also display the maximum violations of the Bell-CHSH inequalities.